Multiple odontogenic keratocysts associated with Gorlin-Goltz syndrome - Dixit, S; Acharya, S; Dixit, PB (Kathmandu University Medical Journal, 2010)
Gorlin-Goltz syndrome or Nevoid basal cell carcinoma syndrome is an autosomal dominant disorder with a predisposition to cancer. Features like basal cell carcinoma, odontogenic keratocysts, calcification of falx cerebri, bifid ribs, pits on palms and soles and hypertelorism are evident. A case of this rare disease seen on a 13 year old female patient is presented here, where multiple odontogenic keratocysts were causing disfigurement of the lower jaw as well as displacement and malocclusion of the lower teeth. Key words: Nevoid basal cell carcinoma syndrome; Gorlin-Goltz syndrome; Odentogenic keratocyst; Calcification of falx cerebri. DOI: 10.3126/kumj.v7i4.2765 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 414-418